First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India - Murthappa, Prashanthakumara S.; Malamel, Jobi J.; Prajapati, Dhruv A.; Sebastian, Pothalil A.; Venkateshwarlu, Mididoddi (Zootaxa, 2017)
The present paper reports the first description of the type species of the theridid genus Meotipa, Meotipa picturata Simon, 1895 and redescribe the female of the same species with one new species Meotipa multuma sp.nov. from India. The two species are described in detail and we provide digital images and illustrations. Chrysso makiling, Barrion-Dupo & Barrion is transferred to Meotipa Simon, 1895 based on the presence of the generic characters of the last genus.